EFFECT OF NIGELLA SATIVA OIL ON BLOOD PRESSURE IN ADULTS WITH HYPERTENSION IN KENDARI INDONESIA - Siti Hadrayanti Ananda; Narmawan Narmawan (Public Health of Indonesia)
Background: Hypertension remains a big challenge for people in Indonesia, especially in adults. Therefore, an effort to reduce high blood pressure is needed. Nigella sativa or known as habbatussauda is one of herbs that is assumed to be able to reduce high blood pressure.